Human umbilical cord-derived mesenchymal stem cells alleviate valproate-induced immune stress and social deficiency in rats - Sun, Shixiong; Luo, Shilin; Chen, Jie; Zhang, Ou; Wu, Qiongying; Zeng, Nianju; Bi, Jinlian; Zheng, Chunbing; Yan, Tenglong; Li, Zhiyuan; Chen, Jindong; Zhang, Yilei; et al. (Frontiers in Psychiatry, 2024)
Introduction Autism spectrum disorders (ASD) are a set of heterogeneous neurodevelopmental disorders characterized by impaired social interactions and stereotypic behaviors. Current clinical care is palliative at the most and there remains huge unmet medical need to fully address the core symptoms of ASD. Human umbilical cord-derived mesenchymal stem cells (hUC-MSCs) are emerging as a promising candidate for ASD treatment, but the precise mechanism remains controversial. Methods In vitro studies we performed the transwell migration assay to explore the interaction between hUC-MSCs and the primary-cultured cortical neurons. Then we determined the therapeutic effects of intravenous administration of hUC-MSCs in rats challenged with valproic acid (VPA) during gestation, a well-defined rat model of autism. Results Our studies showed that hUC-MSCs promoted the growth of primary-cultured cortical neurons. Furthermore, our results demonstrated that hUC-MSCs significantly alleviated microglial activation in the brain, especially in the anterior cingulate cortex, and effectively improved the sociability of the VPA-exposed rats. Discussion These results offer valuable insights for clinical translation and further research on the mechanisms of hUC-MSCs in psychiatric disorders characterized by microglial activation, particularly in cases of autism, shall be warranted.